Automatic Registration of Remote Sensing High-Resolution Hyperspectral Images Based on Global and Local Features - Xiaorong Zhang; Siyuan Li; Zhongyang Xing; Binliang Hu; Xi Zheng (Remote Sensing)
Automatic registration of remote sensing images is an important task, which requires the establishment of appropriate correspondence between the sensed image and the reference image. Nowadays, the trend of satellite remote sensing technology is shifting towards high-resolution hyperspectral imaging technology. Ever higher revisit cycles and image resolutions require higher accuracy and real-time performance for automatic registration. The push-broom payload is affected by the push-broom stability of the satellite platform and the elevation change of ground objects, and the obtained hyperspectral image may have distortions such as stretching or shrinking at different parts of the image. In order to solve this problem, a new automatic registration strategy for remote sensing hyperspectral images based on the combination of whole and local features of the image was established, and two granularity registrations were carried out, namely coarse-grained matching and fine-grained matching. The high-resolution spatial features are first employed for detecting scale-invariant features, while the spectral information is used for matching, and then the idea of image stitching is employed to fuse the image after fine registration to obtain high-precision registration results. In order to verify the proposed algorithm, a simulated on-orbit push-broom imaging experiment was carried out to obtain hyperspectral images with local complex distortions under different lighting conditions. The simulation results show that the proposed remote sensing hyperspectral image registration algorithm is superior to the existing automatic registration algorithms. The advantages of the proposed algorithm in terms of registration accuracy and real-time performance make it have a broad prospect for application in satellite ground application systems.